-4(y-9)=-10(2-y)

Simple and best practice solution for -4(y-9)=-10(2-y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(y-9)=-10(2-y) equation:


Simplifying
-4(y + -9) = -10(2 + -1y)

Reorder the terms:
-4(-9 + y) = -10(2 + -1y)
(-9 * -4 + y * -4) = -10(2 + -1y)
(36 + -4y) = -10(2 + -1y)
36 + -4y = (2 * -10 + -1y * -10)
36 + -4y = (-20 + 10y)

Solving
36 + -4y = -20 + 10y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-10y' to each side of the equation.
36 + -4y + -10y = -20 + 10y + -10y

Combine like terms: -4y + -10y = -14y
36 + -14y = -20 + 10y + -10y

Combine like terms: 10y + -10y = 0
36 + -14y = -20 + 0
36 + -14y = -20

Add '-36' to each side of the equation.
36 + -36 + -14y = -20 + -36

Combine like terms: 36 + -36 = 0
0 + -14y = -20 + -36
-14y = -20 + -36

Combine like terms: -20 + -36 = -56
-14y = -56

Divide each side by '-14'.
y = 4

Simplifying
y = 4

See similar equations:

| x=4x+2 | | z-1/2=-1/4 | | .3x-4.2=2.4 | | .3-4.2=2.4 | | 60-2x=30 | | 12/18 | | 6-66.6666666667x=-8 | | 19+0+(-9)= | | 6/18+3/19 | | 8/11-4/15 | | 4/9+m=20 | | y=-5x^2+30t+2 | | 2*3*4*5= | | 3x-23=1-4x | | 4/16+2/13 | | 4y+8x=48 | | 3x-2(x+4)=-1 | | 14/15-4/12 | | 5x-11=-11 | | 3/4x+2/9-3/7 | | -4x-21=3x+7 | | 7/20+3/9 | | 2450:345= | | 2-1/2(4x+6)=5x-1 | | 6(-t-1)=9(t-4) | | 9x+5=3x+6 | | 8x+4y=48 | | 11x-3(5x-4)=2+6(x+5) | | 2ln(x)-ln(5)=ln(x+10) | | 6(4+c)=5(c-6) | | 4v^2=-21v-5 | | 84=1x+96 |

Equations solver categories